Rethinking potential output embedding information about the financial cycle - Borio, Claudio E. V. ca. 20./21. Jh; Disyatat, Piti; Juselius, Mikael (BIS working papers, 2013)
This paper argues that incorporating information about the financial cycle is important to improve measures of potential output and output gaps. Conceptually, identifying potential output with non-inflationary output is too restrictive. Potential output is seen as sustainable; yet experience indicates that output may be on an unsustainable path even if inflation is low and stable whenever financial imbalances are building up. More generally, as long as potential output is identified with the non-cyclical component of output fluctuations and financial factors play a key role in explaining the cyclical part, ignoring these factors leaves out valuable information. Within a simple and transparent framework, we show that including information about the financial cycle can yield measures of potential output and output gaps that are not only estimated more precisely, but also much more robust in real time. In the context of policy applications, such "finance-neutral" output gaps are shown to yield more reliable estimates of cyclically adjusted budget balances and to serve as complementary guides for monetary policy. Potential output ; output gap ; financial cycle ; monetary policy ; fiscal policy